Identification of waste: DOWNTIME in the outpatient prescription services at the pharmacy installation of Rumah Sakit Islam Siti Hajar Mataram - Nur Atikah; Sari Nanchi Parhatiwi; Ajeng Dian Pertiwi; Evi Fatmi Utami; Firman Firman (Universitas Islam Indonesia, 2021)
Background: The hospital pharmacy installation is a health service unit that is required to provide professional services and improve quality which is oriented towards achieving patient satisfaction. Waste identification in pharmaceutical services is important because it has an impact on stakeholder satisfaction. Objective: Identifying waste using the DOWNTIME method for the outpatient prescription services at the pharmacy installation of Rumah Sakit Islam Siti Hajar Mataram. Methods: The study used the cross-sectional design, with the population being all outpatients who were provided with pharmaceutical services during February – April 2019 as well as all staff. Data were tabulated and analyzed descriptively. Critical waste was obtained through questionnaires and the root causes of critical waste were obtained through in-depth interviews with 5-why methods.Results: Waste waiting had the highest rate compared to other wastes, reaching 44% or 53 out of 121 respondents, followed by inventory (26%), extra processing (19%), transportation (14%), defects (14%), motion (13%), over production (8%), and non-utilized skills (7%). Meanwhile, from the staff respondents, waiting was also the highest waste (18%), followed by inventory (16%), motion (13%), over production (12%), transportation (12%), non-utilized skills (10%), extra processing (10%), and defects (9%). The root cause of waste waiting was the frequent drug unavailability due to delays in payment of services from the cooperating party to the hospital as well as the narrow service areas.Conclusion:Waste waiting became the critical waste with the highest percentage of dissatisfaction in the patient respondents (44%) and staff respondents (18%).Keywords: Waste, DOWNTIME, outpatient prescription services, pharmacy installation of RSI Siti Hajar MataramIntisari Latar belakang: Instalasi farmasi rumah sakit (IFRS) merupakan unit pelayanan kesehatan yang diharuskan untuk melayani secara profesional dan meningkatkan mutu yang berorientasi pada tercapainya kepuasan pasien. Identifikasi waste dalam pelayanan kefarmasian penting, karena berdampak kepada kepuasan stakeholder. Tujuan: Melakukan identifikasi waste dengan metode DOWNTIME di IFRS Rawat Jalan RSI Siti Hajar Mataram. Metode: Desain penelitian adalah cross sectional, dengan populasi seluruh pasien rawat jalan yang diberikan pelayanan kefarmasian pada bulan Februari–April tahun 2019, dan seluruh staf IFRS. Data ditabulasi dan dianalisis secara deskriptif. Waste kritis diperoleh melalui penyebaran kuisioner dan akar penyebab waste kritis diperoleh melalui wawancara mendalam dengan metode 5 why. Hasil: Waste waiting mendapat angka paling tinggi dibandingkan waste yang lainnya, dimana 44% atau 53 responden dari 121 responden. Kemudian disusul oleh inventory (26%), extra preccesing (19%), transportation (14%), defect (14%), motion (13%), over production (8%) dan non-utilized skill (7%). Bagi responden staf IFRS, waiting juga menjadi waste tertinggi (18%), diikuti oleh inventory (16%), motion (13%), over production (12%), transportation (12%), non-utilized skill (10%), extra processing (10%), dan defect (9%). Akar penyebab waste waiting adalah sering terjadi kekosongan obat akibat keterlambatan pembayaran jasa pelayanan dari pihak kerjasama kepada rumah sakit serta area pelayanan yang sempit. Kesimpulan:Waste waiting menjadi waste kritis dengan persentase ketidakpuasan tertinggi pada responden pasien (44%) dan pada responden staf (18%).Kata kunci :Waste, DOWNTIME, pelayanan resep, pasien rawat jalan, IFRS RSI Siti Hajar Mataram